2018
DOI: 10.1080/02791072.2018.1494869
|View full text |Cite
|
Sign up to set email alerts
|

A Gratuitous Grace: The Influence of Religious Set and Intent on the Psychedelic Experience

Abstract: Psychedelic drugs, or entheogens, have been used for religious purposes among various cultures for thousands of years. Recently, these substances have caught the attention of Westerners for many reasons, including their propensity to induce mystical experiences. This study examined the relationship between religion and having mystical experiences. A total of 119 participants were drawn from psychedelic-related websites and asked to complete an anonymous online questionnaire containing items regarding history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To date, all clinical studies on psilocybin-assisted therapy have evaluated the comprehensive effects of both the compound action and psychotherapy interventions, encompassing rigorous psychological preparation, debriefing sessions, guided support, and environmental manipulations during the administration session . In addition, nonpharmacological factors have been shown to play a crucial role in determining the quality and nature of the subjective experiences associated with psilocybin use in humans, as well as the potential therapeutic outcomes arising from such use. These factors have been referred to as “set and setting”, where “set” refers to mindset and includes psychological and emotional components, such as expectations, mood, personality, and past experiences, and “setting” includes physical components such as the location, lighting, and comfort of the environment, as well as social components such as the presence of other people and their relationship to the individual . Consequentially, the inclusion of these nonpharmacological variables poses a significant challenge to isolation of the biological and pharmacological effects of psilocybin alone through human studies. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all clinical studies on psilocybin-assisted therapy have evaluated the comprehensive effects of both the compound action and psychotherapy interventions, encompassing rigorous psychological preparation, debriefing sessions, guided support, and environmental manipulations during the administration session . In addition, nonpharmacological factors have been shown to play a crucial role in determining the quality and nature of the subjective experiences associated with psilocybin use in humans, as well as the potential therapeutic outcomes arising from such use. These factors have been referred to as “set and setting”, where “set” refers to mindset and includes psychological and emotional components, such as expectations, mood, personality, and past experiences, and “setting” includes physical components such as the location, lighting, and comfort of the environment, as well as social components such as the presence of other people and their relationship to the individual . Consequentially, the inclusion of these nonpharmacological variables poses a significant challenge to isolation of the biological and pharmacological effects of psilocybin alone through human studies. , …”
Section: Introductionmentioning
confidence: 99%
“…Investigation into the clinical use of psilocybin-assisted psychotherapy has shown positive results in the treatment of substance use disorders, end-of-life anxiety, major depressive disorder, and treatment-resistant depression. Although results from these clinical studies have shown positive effects, the underlying mechanisms supporting these long-lasting effects are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation can include completing any outstanding tasks or other activities like, "Quiet reading, relaxation, withdrawal, listening to music, meditation : : : walking, bathingwhatever methods are most effective should be used to produce a serene sense of preparedness" (Metzner & Leary, 1967). Moreover, an individual's intention or motivation for using psychedelics can shape the effects of the experience (Hartogsohn, 2017;Leary et al, 1964;Neitzke-Spruill & Glasser, 2018). Finally, Barber (1970) concluded in his review of the literature that personality influences the intensity of a psychedelic experience and the degree to which one responds with anxiety, paranoia, or hostility.…”
Section: The Development Of Set and Settingmentioning
confidence: 99%
“…Factors pertaining to setting are believed to be even more influential on psychedelic use outcomes (Zinberg, 1984, p. 108). The setting of African American psychedelic users is characterized not only by their minority status in society as a whole, but also by their minority status among the predominately White psychedelic users (Hendricks et al, 2015;Johansen & Krebs, 2015;Neitzke-Spruill & Glasser, 2018;Orsolini et al, 2015). Studies utilizing data from the National Survey on Drug Use and Health (NSDUH) estimate that between 3% and 4% of psychedelic users identify as African American (Hendricks et al, 2015;Johansen & Krebs, 2015;Krebs & Johansen, 2013).…”
Section: Race As a Component Of Set And Settingmentioning
confidence: 99%
See 1 more Smart Citation